Study of a single line of sight gamma ray diagnostics for measurements of the absolute gamma ray emission from JET. (16th December 2021) - Marcer, G.; Nocente, M.; Giacomelli, L.; Gorini, G.; Perelli Cippo, E.; Putignano, O.; Rebai, M.; Rigamonti, D.; Craciunescu, T.; Dal Molin, A.; Kiptily, V.; Kos, B.; et al.
Abstract: The fusion power produced in a DT thermonuclear reactor is currently determined by measuring the absolute 14 MeV neutron yield of the D(T, α )n fusion reaction. Measurements of 17 MeV gamma rays born from the much less probable D(T, 5 He) γ reaction (branching ratio of ∼10 −5 ) have been proposed as an alternative independent method to validate the neutron counting method and also to fulfill the requests of the nuclear regulator for licensing ITER DT operations. However, the development of absolute 17 MeV gamma ray emission measurements entails a number of requirements, such as: (i) knowledge of the 17 MeV gamma ray to 14 MeV neutron emission branching ratio; (ii) the simulation of the gamma ray transport from the extended plasma source to the gamma ray detectors; (iii) a careful determination of the absolute efficiency of previously calibrated gamma ray spectrometers. In this work, we have studied the possibility to infer the global gamma ray emission rate from measurements made with a 3″ × 6″ LaBr3 spectrometer installed at the end of a collimated tangential line of sight at the JET tokamak and using the neutron emission from deuterium plasmas of the most recent experimental campaigns. Results show that 17 MeV gamma ray fluxes at the end of this tangential line of sight have a weak dependence (less than 5%) on the plasma profile and can therefore be used to infer the total emission from the plasma.